1983
DOI: 10.1073/pnas.80.23.7337
|View full text |Cite
|
Sign up to set email alerts
|

Detection of lymphocytes producing a human retrovirus associated with adult T-cell leukemia by syncytia induction assay.

Abstract: Recently 10 T-cell lines were established from patients with adult T-cell leukemia (ATL). During establishment of these cell lines, it was found that when T-cell lines expressing the ATL-associated retroviral antigen were cocultivated with 8C cat cells, multinucleated syncytia were formed. Retroviral antigen-negative T-cell lines did not induce syncytia. Peripheral blood lymphocytes obtained from ATL patients did not express the retroviral antigen before cultivation in vitro but became positive for the retrovi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
75
0
2

Year Published

1984
1984
2005
2005

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 119 publications
(78 citation statements)
references
References 38 publications
1
75
0
2
Order By: Relevance
“…In ATL, it appears that the majority of the leukemic cells do not express viral antigens (32,33) and viral mRNA (34). More recently, using the RT/PCR technique, we (20) and others (29) have shown that viral expression can be detected in the PBMCs of most ATL patients, although this particular technique does not allow discrimination between viral expression occurring in leukemic cells versus the infected circulating normal T cells.…”
Section: Discussionmentioning
confidence: 99%
“…In ATL, it appears that the majority of the leukemic cells do not express viral antigens (32,33) and viral mRNA (34). More recently, using the RT/PCR technique, we (20) and others (29) have shown that viral expression can be detected in the PBMCs of most ATL patients, although this particular technique does not allow discrimination between viral expression occurring in leukemic cells versus the infected circulating normal T cells.…”
Section: Discussionmentioning
confidence: 99%
“…(ii) Cell-to-cell fusion mediated by HTLV-1 Env. Fusion is generally measured by the formation of multinucleated giant syncytial cells (Hoshino et al, 1983;Hildreth et al, 1997;Tajima et al, 1997), or by an adaptation of an HIV Tat-based assay (Rocancourt et al, 1990) in which Env-receptor interactions are revealed by the transfer of HIV Tat molecules to indicator cells harboring a Tat-dependent marker gene (Denesvre et al, 1995). The latter appears more suited to directly evaluate receptor function, since several cell lines that are fully susceptible to HTLV-1 Env-mediated viral entry are resistant to syncytia formation (Kim et al, 2003).…”
Section: The Htlv Receptor Enigmamentioning
confidence: 99%
“…Moreover, viral pseudotypes bearing HTLV-I or HTLV-II envelope glycoproteins can penetrate a variety of mammalian cell lines (24). In several of these susceptible cells, syncytia were induced by cocultivation with HTLV-I-producing cells (25,26) and in a single human osteosarcoma cell line stable HTLV-I replication could be demonstrated (27).…”
mentioning
confidence: 99%